Issues on intelligent electronic agents and legal relations - Andrade, Francisco Carneiro Pacheco (2004)
computers have been looked as an instrument due to process and record information, but also as a means of automatically processing and transmitting information, and now as a means of autonomously thinking, deciding, acting. Recent trends in the field of what we are calling Artificial Intelligence, brought along new ways of expressing will and declarations – as an electronic behaviour that exteriorizes the content of a certain autonomous will. This leads us to a urgent need of rethinking many legal theories that we had since long ago already thought as definitely established, such as the theories of will, personality, consent and representation. In this paper we will question legal relations involving Intelligent Electronic Agents.